Introduction to human communication : perception, meaning, and identity - Beauchamp, Susan R.; Baran, Stanley J. (2020)
"Introduction to Human Communication shows how effective communication is central to shared meaning-making, identity construction and maintenance, and responsible interaction with the world. In an inviting and engaging style, Beauchamp and Baran provide the most current and complete survey of the discipline. They cover the basics of communication theory and research with vivid examples while providing practical tools to help students become more thoughtful, confident, and ethical communicators. The text demonstrates the relevance of communication to our everyday lives and invites students to apply what they learn in a broad variety of contexts, including mass communication, organizational communication, health communication, social media, and media literacy"--
The communication process: perception, meaning, and identity -- Communication research and inquiry -- Verbal communication -- Nonverbal communication -- Listening -- Relational and conflict communication -- Communicating in small groups -- Organizational communication -- Intercultural communication -- Mass communication -- Media literacy -- Social media and communication technologies -- Persuasion and social influence -- Health communication -- Public speaking: an overview.
Includes bibliographical references.
Keywords: Communication; Interpersonal communication